2016
DOI: 10.1073/pnas.1512955113
|View full text |Cite
|
Sign up to set email alerts
|

Genomic incompatibilities in the diploid and tetraploid offspring of the goldfish × common carp cross

Abstract: Polyploidy is much rarer in animals than in plants but it is not known why. The outcome of combining two genomes in vertebrates remains unpredictable, especially because polyploidization seldom shows positive effects and more often results in lethal consequences because viable gametes fail to form during meiosis. Fortunately, the goldfish (maternal) × common carp (paternal) hybrids have reproduced successfully up to generation 22, and this hybrid lineage permits an investigation into the genomics of hybridizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 77 publications
1
87
1
1
Order By: Relevance
“…There was apparently only one autotetraploidization event that occurred at the common ancestor of salmonids approximate 80 Mya, while polypoloidization evolved independently on multiple occasions in Cyprinids, of which the common carp (Cyprinus carpio) and goldfish (Carassius sp.) appear to have experienced the latest allotetraploidization event before their divergence [13][14][15] , thus providing an excellent model system for investigating the initial allopolyploidization event in teleosts and understanding the evolutionary Green, yellow and red circles represent the teleost-specific whole genome duplication (Ts3R), salmonid-specific whole genome duplication (Ss4R) and carp-specific whole genome duplication (Cs4R), respectively. benefits for phenotypic plasticity, environmental adaptations and species radiation post the latest WGD.…”
Section: Introductionmentioning
confidence: 99%
“…There was apparently only one autotetraploidization event that occurred at the common ancestor of salmonids approximate 80 Mya, while polypoloidization evolved independently on multiple occasions in Cyprinids, of which the common carp (Cyprinus carpio) and goldfish (Carassius sp.) appear to have experienced the latest allotetraploidization event before their divergence [13][14][15] , thus providing an excellent model system for investigating the initial allopolyploidization event in teleosts and understanding the evolutionary Green, yellow and red circles represent the teleost-specific whole genome duplication (Ts3R), salmonid-specific whole genome duplication (Ss4R) and carp-specific whole genome duplication (Cs4R), respectively. benefits for phenotypic plasticity, environmental adaptations and species radiation post the latest WGD.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that there was sequence divergence after autotetraploidization. Previous studies suggested that polyploid formation could induce various types of genomic changes (Chen & Pikaard, 1997;Ha et al, 2009;Kashkush et al, 2003;Leitch & Leitch, 2008;Liu et al, 2016a;Ozkan et al, 2001;Parisod et al, 2010;Qin et al, 2010Qin et al, , 2016aSong et al, 1995;Tate et al, 2006). Importantly, a variety of genomic changes has been shown to result in diploid-like chromosome pairing (Paterson et al, 2004;Soltis et al, 2009;Wendel, 2000;Wolfe, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several types of allotetraploid gibel carp with over 200 chromosomes have been created in the past thirty years (Gui et al., a; Zhu & Gui, ; Xiao et al., ; Li, Liang et al., ; Liu, Sun, Zhang, Luo & Liu, ; Liu et al., ). In this study, a newly synthetic allopolyploid strain was identified to have 206 chromosomes, and the morphological and growth traits were evaluated (Figure ).…”
Section: Discussionmentioning
confidence: 99%